Thermochronological Evidence of Early Orogenesis, Eastern Pyrenees, France. Issue 4 (10th April 2019) - Ternois, Sébastien; Odlum, Margaret; Ford, Mary; Pik, Raphaël; Stockli, Daniel; Tibari, Bouchaïb; Vacherat, Arnaud; Bernard, Vincent
Abstract: In collisional orogens, distinguishing the thermal signature of early orogenesis from the preceding rift or from subsequent thermal events is a major challenge. We present an integrated geological and low‐temperature thermochronology study of the Paleozoic Agly‐Salvezines crustal block in the retrowedge of the eastern Pyrenees (France). The northern Pyrenees preserves one of the best geological records of a rift‐to‐collision transition. The Agly‐Salvezines block represents the inverted distal European margin of an Aptian–Cenomanian rift system. Seventeen samples were collected throughout the external orogenic massif and analyzed for low‐temperature thermochronology: zircon (U‐Th)/He dating documents the cooling history of the massif during the initiation and early phase of Pyrenean convergence, while apatite (U‐Th)/He dating completes the record of plate collision. Using inverse and forward modeling of new low‐temperature thermochronology data, we show that the Pyrenean retrowedge records two clear phases of orogenic cooling, Late Campanian–Maastrichtian and Ypresian–Bartonian, which we relate to early inversion of the distal rifted margin and main collision, respectively. An earlier, late Aptian–Turonian cooling history is detected, possibly related to rifting and/or postrift. No cooling is evidenced during the Paleocene during which tectonic quiescence is recorded in the adjacent Aquitaine retroforeland basin. Using our low‐temperature thermochronology data and geological constraints, we propose a crustal‐scale sequentially restored model for the tectonic and thermal transition from extension to peak orogenesis in the eastern Pyrenees, which suggests that both thrusting and underplating processes contributed to early inversion of the Aptian–Cenomanian rift system. Key Points: Zircon (U‐Th)/He data record a cooling phase during early convergence in the Pyrenean low‐relief retrowedge (Agly‐Salvezines block) Forward and inverse thermal history modeling reveals limitations in current radiation damage‐annealing models for He diffusion in zircon Crustal section sequential restoration demonstrates that tectonic processes alone can generate rapid cooling during early orogenesis